The Listening and Reading Interactive Model: A Strategy to design Communicative Activities Through Passive Skills - Schnell, Eva (2016)
This article is intended to incorporate the Interactive Listening and Reading Model, from the perspective of Swaffar, Arens and Byrnes (1991) as a strategy and thread to develop, organize and scale up the activities of a teaching unit or lesson plan. This with the intention of highlighting the Model as an integrative tool providing opportunities to select and organize a motivating repertoire with interactive, meaningful and contextualized activities starting from the area of comprehension (listening and reading), including also expressive activities (oral and written) as well as cognitive aspects to generate meaning, recreation and reaction to the text from a personal perspective.